2013
DOI: 10.1002/jca.21255
|View full text |Cite
|
Sign up to set email alerts
|

Acquired hemoglobin variants and exposure to glucose‐6‐phosphate dehydrogenase deficient red blood cell units during exchange transfusion for sickle cell disease in a patient requiring antigen‐matched blood

Abstract: Red blood cell exchange (RBCEx) is frequently used in the management of patients with sickle cell disease (SCD) and acute chest syndrome or stroke, or to maintain target hemoglobin S (HbS) levels. In these settings, RBCEx is a category I or II recommendation according to guidelines on the use of therapeutic apheresis published by the American Society for Apheresis. Matching donor red blood cells (RBCs) to recipient phenotypes (e.g., C, E, K-antigen negative) can decrease the risk of alloimmunization in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…16,17 Functionally relevant RBC polymorphisms are anticipated to be high in donors with racial origin or admixture from malaria-endemic regions, such as equatorial Africa, Asia, and South and Central America. 18 In these donors, certain conserved RBC mutations that historically conferred resistance against malaria may impact RBC functional characteristics and be disadvantageous with regard to cold storage.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Functionally relevant RBC polymorphisms are anticipated to be high in donors with racial origin or admixture from malaria-endemic regions, such as equatorial Africa, Asia, and South and Central America. 18 In these donors, certain conserved RBC mutations that historically conferred resistance against malaria may impact RBC functional characteristics and be disadvantageous with regard to cold storage.…”
Section: Introductionmentioning
confidence: 99%
“…The criteria for the selection of blood donors do not exclude the presence of this genetic disorder, and it was observed that specific donor RBC units are more likely to haemolyse during storage . Transfusion outcomes of RBC units from G6PD‐deficient donors have been recently discussed especially for high risk patients as premature infants and neonates, and patients with sickle cell disease (SCD) submitted to multiple transfusions . Moreover, checking for the presence of G6PD deficiency in blood donors or in RBC units was suggested in the regions with high frequency of G6PD deficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Raciti et al [1] recently described a patient with sickle cell disease requiring chronic transfusion support, who was passively transfused with hemoglobin C (HgbC), hemoglobin G-Philadelphia, and glucose-6phosphate dehydrogenase deficient RBC units all of which were antigen-matched to reduce the likelihood of alloimmunization. We would like to share our experience with a similar patient.…”
Section: To the Editormentioning
confidence: 99%
“…As mentioned by Raciti et al [1], we too considered the consequences of antigen-matching for this patient. Donors negative for K1, S, and Fy a antigens are significantly more common among black donors (60% versus 15% white) [2], thus increasing the likelihood of transfusion with HgbC.…”
Section: To the Editormentioning
confidence: 99%